B cells promote induction of experimental autoimmune encephalomyelitis by facilitating reactivation of T cells in the CNS - Pierson, Emily R. (2013)
The efficacy of rituximab treatment in multiple sclerosis has renewed interest in the role of B cells in CNS autoimmunity. Here we show that B cells are the predominant MHC class II(+) subset in the naïve CNS in mice, and they constitutively express pro-inflammatory cytokines. Incidence of experimental autoimmune encephalomyelitis (EAE) induced by adoptive transfer was significantly reduced in C3HeB/Fej μMT (B cell-deficient) mice, suggesting an important role for CNS B cells in initiating inflammatory responses. Initial T cell infiltration of the CNS occurred normally in μMT mice; however, lack of production of T cell cytokines and other immune mediators indicated impaired T cell reactivation. Subsequent recruitment of immune cells from the periphery driven by this initial T cell reactivation did not occur in μMT mice. B cells required exogenous IL-1β to reactivate Th17 but not Th1 cells in vitro. Similarly, reactivation of Th1 cells infiltrating the CNS was selectively impaired compared to Th17 cells in μMT mice, causing an increased Th17:Th1 ratio in the CNS at EAE onset and enhanced brain inflammation. These studies reveal an important role for B cells within the CNS in reactivating T cells and influencing the clinical manifestation of disease.